2021
DOI: 10.3389/fmars.2021.649378
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Incorporated With Causal Analysis for Short-Term Prediction of Sea Ice

Abstract: Accurate and fast prediction of sea ice conditions is the foundation of safety guarantee for Arctic navigation. Aiming at the imperious demand of short-term prediction for sea ice, we develop a new data-driven prediction technique for the sea ice concentration (SIC) combined with causal analysis. Through the causal analysis based on kernel Granger causality (KGC) test, key environmental factors affecting SIC are selected. Then multiple popular machine learning (ML) algorithms, namely self-adaptive differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The BN-based assessment model is an intelligent model and we focus on comparing it with other intelligent assessment models. At present, BPNN and SVM have achieved successful applications in the field of risk assessment (Feng and Liu, 2017;Li et al, 2021a Figure 6 displays the disaster assessment results of the three models. The assessment accuracy of BPNN and SVM are 61.34 and 70.67%, respectively, which are significantly lower than the accuracy of BN (91.03%).…”
Section: Comparison With Other Intelligent Assessment Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BN-based assessment model is an intelligent model and we focus on comparing it with other intelligent assessment models. At present, BPNN and SVM have achieved successful applications in the field of risk assessment (Feng and Liu, 2017;Li et al, 2021a Figure 6 displays the disaster assessment results of the three models. The assessment accuracy of BPNN and SVM are 61.34 and 70.67%, respectively, which are significantly lower than the accuracy of BN (91.03%).…”
Section: Comparison With Other Intelligent Assessment Modelsmentioning
confidence: 99%
“…Through systematic analysis of risk-causing factors and riskbearing bodies of marine disasters, Li et al (2018b) adopted the BN and gray relational analysis to build a risk assessment model. Then, Li et al (2020;2021a) also proposed the improved weighted BN to mine the causal relationship of disaster factors and realized probabilistic reasoning of marine disaster risk.…”
Section: Introductionmentioning
confidence: 99%
“…McGraw et al [25] examined the causal relationship between Arctic sea ice and atmospheric circulation using Granger causal analysis. Li et al [26] developed a new data-driven prediction technique for sea ice density by screening the key environmental factors affecting the sea ice density through causal analysis based on the Granger causality test. Liang et al [27] demonstrated that the South China Sea significantly influences the Pacific-North America remote sensing model, using the causal inference of information flow.…”
Section: Introductionmentioning
confidence: 99%